PROBLEMS OF REAL ESTATE AUDITING. - Taggart, H. F. (The Accounting Review, 1926)
One who undertakes to audit the books of real estate concerns is apt to run afoul of situations as complicated and obscure as it is possible to imagine. The most ingenious inventor of Certified Public Accountant questions could furnish no worse tangles than are to be found in the accounts of this type of business. The examiner is under the handicap of having to produce most, at least, of the salient facts in plain black and white, whereas the details of much that goes on in a real estate office are hidden away in the terms of some lengthy contract, or, worse, lie buried in the memories of the several persons who took part in the transactions, each one of whom may have a different recollection of what took place. The process of determining the true history of the deal was so like fitting together the irregular sections of a picture puzzle that simile may conveniently be used. In two respects this puzzle was more difficult than the ordinary one. In this case the parts had first to be found before they could be placed in the proper juxtaposition. Furthermore, while the usual puzzle is accompanied by a completed picture showing what the result will be when the pieces are correctly placed, this feature was lacking in the present case. All that was to be had was the assurance that when the pieces were found and brought together in the proper manner a picture would result.